Approbation of Pedagogical Communication Scales for Educational Online Interaction in Russian Universities - Natalia Riapina; Tatyana Permyakova; Ekaterina Balezina (Вопросы образования, 2023)
The current study is set to test pedagogical communication scales, specifically the teacher clarity scale and the teacher immediacy scale as being the most significant for the educational online interaction.  The impact of teacher clarity and immediacy on cognitive, affective, and behavioral learning outcomes is shown. 409 undergraduate students (117 men and 286 women, average age - 20, SD = 2.1) completed survey instruments. Self-reported measures were used to evaluate their perceptions of teacher clarity and immediacy in the online learning process as well as students’ preparedness to use the behaviours recommended in the course. Furthermore, the relationships between instructor clarity and immediacy were investigated. The findings indicate that teacher clarity and immediacy had a direct correlation with cognitive, affective, and behavioural learning outcomes as well as with students’ intentions to use behavioral patterns recommended in the course.  The paper sheds new light on instructional practice. Teachers can be recommended to consider clarity and immediacy of their communication with students in the online learning environment, as these characteristics contribute to the effectiveness in online learning.